Release of natural extracts from PVA and PVA-CMC hydrogel wound dressings: a power law swelling/delivery - Oliveira, Renata Nunes; Meleiro, Luiz Augusto da Cruz; Quilty, Brid; McGuinness, Garrett Brian (Frontiers in Bioengineering and Biotechnology, 2024)
The present work aims to study the physical, mechanical and release characteristics of hydrogel wound dressings loaded with either of two natural herbal products. PVA matrices incorporating sage extract or dragon's blood (DB) present hydrogen bonding between these components. PVA-CMC hydrogels containing sage present similar spectra to PVA-CMC alone, probably indicating low miscibility or interaction between the matrix and sage. The opposite is found for DB, which exhibits more pronounced interference with crystallinity than sage. DB and NaCMC negatively affect Young's modulus and failure strength. All samples appear to reach equilibrium swelling degree (ESD) in 24h. The addition of DB and sage to PVA increases the gels' swelling capacity, indicating that the substances likely separate PVA chains. The inclusion of CMC contributes to high media uptake. The kinetics profile of media uptake for 4 days is described by a power-law model, which is correlated to the drug delivery mechanism. A PVA-CMC gel incorporating 15% DB, the highest amount tested, shows the most favorable characteristics for flavonoid delivery, as well as flexibility and swelling capacity.